Sheffield Adaptive Patterned Electrical Stimulation (SHAPES) Therapy for Post Stroke Arm spasticity: study protocol for a 3-arm, a partially blinded, randomised controlled trial - Ali Ali; Avril D. McCarthy; Mark Reeves; Jamie Healey; Louise Moody; Adewale Adebajo; Tim Good; Simon Dixon; Kathleen Baster; Wendy Tindale; Krishnan Padmakumari Sivaraman Nair (BMC Neurology)
Abstract Introduction Post stroke elbow spasticity (PSES) affects over a third of individuals following stroke and negatively impacts on functional recovery, comfort and quality of life. Drug therapies have limited efficacy and unwanted side effects, botulinum toxin, although effective, is costly, and conventional electrical stimulation therapies are limited long term by habituation. We aim to investigate the efficacy of Sheffield Adaptive Patterned Electrical Stimulation (SHAPES), that delivers temporally and spatially varying pattern of electrical stimulation, against transcutaneous electrical stimulation (TENS) and standard care at reducing PSES. Methods and design Overall, 297 people with PSES will be randomised (1:1:1) to one of 3 arms: Standard care (no electrical stimulation), TENS (conventional patterned electrical stimulation) or SHAPES (adaptive patterned electrical stimulation). Both SHAPES and TENS are delivered using a specially designed electrical stimulation sleeve used for 60 min each day for 6-weeks. Outcome measures are completed at baseline, end of treatment (EOT 6 weeks) and then 6-weeks, 12-weeks and 24-weeks after the end of treatment. Efficacy will be determined based on the proportion of participants experiencing meaningful improvement (18%) in the 7-day Numerical Rating Scale (NRS-S) for PSES, compared between both intervention arms and standard care, and between the two intervention groups. Measures of arm motor function (Action Research Arm Test, MRC scale), and quality of life (SQoL-6D, EQ-5D) will also be measured along with a parallel health economic evaluation. Discussion The results of the SHAPES trial will inform management of elbow spasticity after stroke. The SHAPES intervention is a low cost, self-administered intervention for the management of spasticity that can be used repeatedly, and if found to be more effective than TENS or control has the potential to be widely implemented in the UK NHS healthcare setting. Furthermore, despite the wide use of TENS in the management of spasticity, this study will provide critically required evidence regarding its efficacy. The trial has been registered with the ISRCTN registry (ISRCTN26060261).